2018
DOI: 10.3390/ijerph15050983
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Shoe Fitting and Foot Health of Persons with Down Syndrome: A Case Control Study

Abstract: Background: Down syndrome is the most common chromosomal abnormality and a cause of intellectual disability. It is also associated with orthopaedic and musculoskeletal problems of the locomotive apparatus, especially of the feet. These problems are believed to have a harmful effect on health, social functioning, and mobility. In addition, these persons generally don’t have access to podiatric health services, even when their foot problems are well known, because of limited access to healthcare facilities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In first place, the conception that the connectivity patterns study with fMRI signal in resting situation seem to be an adequate mechanism for the study of the brain functioning in people who have cognitive difficulties and which a task realization could compromise the result. Much has been discussed [ 9 ] on this issue, and, in the case of people with DS, it seems that the idea should be maintained. The resting situation in a brain signal recording is a good cognitive evaluation option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In first place, the conception that the connectivity patterns study with fMRI signal in resting situation seem to be an adequate mechanism for the study of the brain functioning in people who have cognitive difficulties and which a task realization could compromise the result. Much has been discussed [ 9 ] on this issue, and, in the case of people with DS, it seems that the idea should be maintained. The resting situation in a brain signal recording is a good cognitive evaluation option.…”
Section: Discussionmentioning
confidence: 99%
“…The eight dimensions of this model have been empirically validated in different cultures and countries [ 2 , 3 , 4 ] and are organized into three higher-order factors [ 4 ]: (1) independence, which includes the dimensions of personal development and self-determination; (2) social Participation, which includes dimensions of interpersonal relations, social inclusion, and rights; and (3) well-being, which includes the dimensions of emotional well-being, physical well-being, and material well-being. This concept has become a social construct that provides a reference for assessing the impact of processes and services addressed to this population [ 5 , 6 , 7 , 8 ], and, together with the studies related to health levels [ 9 , 10 ], they have become one of the most mentioned topics in this field. Accordingly, most of works focused on QoL analyze the characteristics of the inputs and in the measurement procedure in itself; however, little is investigated about other effects emerged related with QoL.…”
Section: Introductionmentioning
confidence: 99%
“…The use of shoes with an incorrect length can cause foot injuries [5,9,13,42,43]. Menz et al [44] observed, in a geriatric population, that when looking for an adequate adjustment to the width of the foot, shoes longer than the usual recommendations were chosen.…”
Section: Discussionmentioning
confidence: 99%
“…Kouchi [11] suggested that to reduce the pressure on the lateral edge of the forefoot, it is necessary to change the curvature of the latter [12]. Calvo-Lobo et al [13] evaluated the length and width to assess the fit of footwear taking into account the studies of Kouchi [11]. To achieve a good fit, it is necessary to assess the curvature of the footwear, especially since those with Down syndrome are mostly flatfooted.…”
Section: Introductionmentioning
confidence: 99%
“…A physical examination of the foot and ankle was carried out to determine the presence of podiatric pathologies. The general health of the foot was evaluated, observing the state of the skin, and giving attention to the presence of hyperkeratosis or nail diseases 37 .…”
Section: Methodsmentioning
confidence: 99%